Co-Ultramicronized Palmitoylethanolamide/Luteolin-Induced Oligodendrocyte Precursor Cell Differentiation is Associated With Tyro3 Receptor Upregulation - Facci, Laura; Barbierato, Massimo; Fusco, Mariella; Giusti, Pietro; Zusso, Morena (Frontiers in Pharmacology, 2021)
Remyelination in patients with multiple sclerosis frequently fails, especially in the chronic phase of the disease promoting axonal and neuronal degeneration and progressive disease disability. Drug-based therapies able to promote endogenous remyelination capability of oligodendrocytes are thus emerging as primary approaches to multiple sclerosis. We have recently reported that the co-ultramicronized composite of palmitoylethanolamide and the flavonoid luteolin (PEALut) promotes oligodendrocyte precursor cell (OPC) maturation without affecting proliferation. Since TAM receptor signaling has been reported to be important modulator of oligodendrocyte survival, we here evaluated the eventual involvement of TAM receptors in PEALut-induced OPC maturation. The mRNAs related to TAM receptors Tyro3, Axl, and Merkt were all present at day 2 in vitro. However, while Tyro3 gene expression significantly increased upon cell differentiation, Axl and Mertk did not change during the first week in vitro. Tyro3 gene expression developmental pattern resembled that of MBP myelin protein. In OPCs treated with PEALut the developmental increase of Tyro3 mRNA was significantly higher as compared to vehicle while was reduced gene expression related to Axl and Mertk. Rapamycin, an inhibitor of mTOR, prevented oligodendrocyte growth differentiation and myelination. PEALut, administered to the cultures 30 min after rapamycin, prevented the alteration of mRNA basal expression of the TAM receptors as well as the expression of myelin proteins MBP and CNPase. Altogether, data obtained confirm that PEALut promotes oligodendrocyte differentiation as shown by the increase of MBP and CNPase and Tyro3 mRNAs as well as CNPase and Tyro3 immunostainings. The finding that these effects are reduced when OPCs are exposed to rapamycin suggests an involvement of mTOR signaling in PEALut effects.